Computational intelligence the experts speak - Fogel David B; Robinson Charles J (New Jersey IEEE Press, 2003)
It represents the collective current state of research in neural networks, fuzzy systems, and evolutionary computation.It also covers an array of leading-edge applications, from coevolutionary robotics to underwater sensors and cognitive science in such
Keywords: Artificial intelligence; Computational intelligence